SEM Observation on Fracture Surface of Coconut Fibers Reinforced Polyester Composite - Badri, Muftil; Sugiman, Sugiman; Aguswandi, Aguswandi; Jayadi, Jayadi (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2017)
The fracture behavior of coconut fibers reinforced polyester composite depends on different fibers orientation was experimentally investigated under static loading conditions. The static uniaxial tensile and flexural loading for three (random discontinuous, longitudinal and woven direction) coconut fibers reinforced polyester composite was implemented using servo hydraulic material testing machine. The microstructure was observed using SEM observation in order to better understand damage mechanism during the stress of polyester phase. SEM observation on fracture surface can provide important information for research and development as well as fracture analysis. It was found that fracture modes were considerably different for these composites. The random discontinuous coconut fibers composite fracture caused by defects in fiber pull out, the longitudinal coconut fibers composite fracture caused by matrix cracking and delamination, the woven coconut fibers fracture caused by debonding and void. Based on the SEM observation results, the fracture behavior was determined and it was found that static loading conditions and fiber direction influence the fracture surface of coconut fibers reinforced polyester composite.